2014
DOI: 10.4321/s1135-57272014000600009
|View full text |Cite
|
Sign up to set email alerts
|

Infección VIH/Sida y otras infecciones de transmisión sexual en la población inmigrante en España: revisión bibliográfica

Abstract: RESUMENFundamentos: Los flujos migratorios tienen la capacidad de dispersar agentes infecciosos y alterar las epidemiologías locales. El objetivo del estudio es describir las características socio-epidemiológicas, clínicas y de microbiología/epidemiología molecular de la infección VIH/Sida en la población inmigrada.. Métodos:Revisión de la literatura científica mediante la metodología de Scoping Review. Se realizó una búsqueda bibliográfica en las bases de datos Medline y MEDES. Se seleccionaron artículos orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
2
2
0
1
Order By: Relevance
“…If to the fact of being a woman, the fact of being a foreigner is added, the likelihood of being diagnosed with a STI in our study increased even more. This result confirms the findings in previous Spanish studies where immigrant women were more exposed to HIV infection [ 32 , 33 ]. In this sense, the last report on Epidemiologic Surveillance of HIV and AIDS in Spain states that among the foreign population with new HIV diagnoses, 56% were women, had a worse immunological response to antiretroviral therapy, showed less follow-up, and less time for therapeutic failure [ 63 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…If to the fact of being a woman, the fact of being a foreigner is added, the likelihood of being diagnosed with a STI in our study increased even more. This result confirms the findings in previous Spanish studies where immigrant women were more exposed to HIV infection [ 32 , 33 ]. In this sense, the last report on Epidemiologic Surveillance of HIV and AIDS in Spain states that among the foreign population with new HIV diagnoses, 56% were women, had a worse immunological response to antiretroviral therapy, showed less follow-up, and less time for therapeutic failure [ 63 ].…”
Section: Discussionsupporting
confidence: 92%
“…In relation to the sociodemographic characteristics of the sample analyzed, it is noted that the mean age of individuals diagnosed with an STI was lower than in the case of those who did not have them. This result coincides with the publications in the scientific literature, considering the young population as one of the groups most exposed to STIs [ 22 , 23 , 24 ] along with other vulnerable groups such as gay men [ 5 , 25 , 26 , 27 , 28 ], men who have sex with men (MSM), transgender people, injecting drug users, women, sex workers, and immigrants, especially irregular immigrants [ 18 , 29 , 30 , 31 , 32 , 33 ]. Likewise, in a recent study on HIV and other STI epidemiology, it is observed that in 2006 the higher number of cases of some STIs such as syphilis, gonorrhea, chlamydia trachomatis, and lymphogranuloma venereum occurred in young adults between 25–44 years old [ 34 ], the age range in which the mean age of persons positively diagnosed with STIs is found in our study.…”
Section: Discussionsupporting
confidence: 88%
“… 16 , 17 Subsequently HIV prevalence is often much higher in this subgroup. 16 18 Although HIV infection increases the risk to acquire or reactivate TB, only few studies report on the epidemiology of TB amongst transgenders. 19…”
Section: Discussionmentioning
confidence: 99%
“…19 Este calendario fue análogo en Europa Occidental y Norteamérica, 20 en cambio, en los países con menor y más tardío acceso a TARGA -caso del sudeste asiático y el África subsahariana-el impacto negativo fue mayor y la recuperación de esperanza de vida se inició alrededor de 2010. 20,21 La importancia de las campañas de concienciación y prevención y de las prácticas médicas en su conjunto fue fundamental para la cronificación de la infección por VIH y el descenso de la mortalidad por sida. Sin embargo, actualmente quedan retos pendientes: la mayor prevalencia en población de origen migrante 22,23 y la restricción de su acceso a servicios relacionados con el VIH, 24 el incremento de conductas sexuales de riesgo en colectivos de jóvenes y de hombres homosexuales, 25 los indicios de diagnóstico tardío en nuevas infecciones 26,27 y el incremento de mortalidad por enfermedades asociadas con el VIH que no son sida, 6 efecto inevitable de la efectividad del TARGA.…”
Section: Artículo Breveunclassified